PREVALANCE OF HEPATITIS C VIRUS ANTIBODIES IN DIFFERENT GROUPS - Hüseyin TURGUT,; Mine TURHANOĞLU,; Kemalettin AYDIN,; Eralp ARIKAN,; Halil DEĞERTEKİN,; Sedat ARITÜRK, (Turkish Journal of Gastroenterology, 2020)
-